Penderitaan sebagai Pengalaman Eksistensial dalam Konsep Manusia Partisipan Menurut Gabriel Marcel: Suffering as an Existential Experience in the Concept of Participatory Humanity According to Gabriel Marcel - Turut, Yonesmus Rikardus; Riyanto, F. X. E. Armada (Jurnal Filsafat Indonesia, 2025)
The focus of this paper is to explore Gabriel Marcel's thinking on suffering as an existential experience that involves human participation in facing the realities of life. Suffering is often seen as a painful and destructive burden in human life, yet in Marcel's view, suffering is not merely a problem to be solved, but a "mystery" that opens up space for deep reflection, spiritual growth, and solidarity. Through the concept of the participative human, Marcel emphasizes the importance of active involvement in the world, both physically and mentally, to build intersubjective relationships that enrich the experience of suffering. This participation allows individuals to move beyond isolation and see suffering as a collective experience that can provide meaning through connection with others and God. This research uses a literature study method to analyze Marcel's views on suffering and its relevance to contemporary life, which is filled with various forms of suffering. This paper finds that through participation, suffering can be understood not only as a personal burden but also as an opportunity to strengthen human relationships and achieve a deeper understanding of the meaning of life and human existence.